The Construction of an Assessment Index System of Law-Based Governance of a City in China - Ze Li; N. Symaniuk (BRICS Law Journal)
Constructing an assessment index system of law-based governance of a city provides a data basis and an empirical basis for China’s urban construction of the rule of law and highlights its characteristics in the era of big data. A thorough understanding of the theory of the rule of law is required in order to establish this index system. The establishment of the index system needs to be based on a deep understanding of the theory of the rule of law. In particular, it is important to understand the relationship between the core content of the rule of law and the law-based governance of a city, and then to determine the connotation of law-based governance of a city. This serves as the starting point for constructing the index system. At the same time, it is necessary to have a solid grasp of the index theory, adhere to the method of index setting, break down the concept of law-based governance of a city into different levels of indicators according to the types and attributes of the indicators and continue to visualize and operationalize them until the content can be measured. As a whole, this forms a complete assessment index system. Of course, the content of the index system is not fixed and needs to be constantly tested and adjusted in practice.